Design and development of the diabestfriend android application for type 2 diabetes self-care management - Alkharis, Vira Zahra; Asiandi, Asiandi; Purwandari, Ristiana Dyah; Supriyadi, Supriyadi (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2025)
Background: Effective self-care management is essential for controlling type 2 diabetes mellitus (T2DM); however, many existing mobile health applications lack comprehensive and guideline-based features aligned with core diabetes self-care pillars. Purpose: This study aimed to design, develop, and evaluate the feasibility of the diabestfriend android application as a digital self-care management tool for patients with T2DM. Methods: A research and development (R&D) study using the ADDIE model (analysis, design, development, implementation, and evaluation) was conducted. Application features were developed based on the Indonesian endocrinology association diabetes self-care guidelines. Feasibility was assessed through expert validation by media and content experts and user experience evaluation among patients with T2DM. Results: Media expert validation rated the application as excellent (score: 83.8), while content expert validation indicated a very good rating (score: 81.6). Feature feasibility testing among 22 users demonstrated that the application successfully supported structured data entry for blood glucose monitoring, diet management, physical exercise, and medication reminders. User experience evaluation involving 10 patients with T2DM showed high acceptability, with an overall satisfaction score of 88.95%, highlighting ease of navigation, clarity of educational materials, and usefulness of reminder features. Conclusion: The Diabestfriend application demonstrates strong feasibility and usability and is suitable for use as a comprehensive digital self-care management tool for patients with T2DM.